The stories we tell ourselves: Joan Didion on the romantic fantasies of reality - Nicholson, Sabrina Sky (Department of English Language and Literature, 2022)
This dissertation attempts to showcase the ways in which Joan Didion employs metaphoric prose to expose the “romantic fantasies” in the creative nonfiction works of Slouching Towards Bethlehem (1968) and The Year of Magical Thinking (2005). I propose that a reading of these romantic fantasies is dependent on the distinction between “romantic” (lower case) and “Romantic” (capitalized). While Didion explores “romantic” fantasies of contemporary American existence that consist of society's idealized notions of reality, happiness and morality, I simultaneously argue the extent to which she borrows sentiments from the Romantic period in her writing, further strengthening her thematic content that deals with the notion of disorder. I showcase her use of literary techniques as well as popular ideologies essential to Romanticism, such as the emphasis on introspection and the imagination. This dissertation departs from J.R.R. Tolkien's (1947) theories on fantasy which portrays the imagination of an individual as a reflection of one's desires. This serves to offer some justification underlying the basis of romantic fantasies, illustrated by Didion's own personal account of her subjection to magical thinking — a type of thinking rooted in James George Frazer's theoretical framework of Sympathetic Magic (1911). The significance of this is to demonstrate what Sara Ahmed (2010) rationalizes as society's estrangement from happiness in the pursuit of an idealized version of happiness that is only accessible through one's imaginative capacities. Through a literary analysis of Didion's metaphoric prose, I employ Mark Muggli's (1987) analysis of Didion's use of emblem as extreme in its power to transcend the confines of her narratives in a process that demands a cognitive interpretation from her reader. I argue that her metaphoric prose, embedded in emblematic imagery, affords the reader a sense of agency in contributing their own perspectives in the decoding of her language that she leaves, at times, quite ambiguous, allowing for the reader to form their own deductions. Through this, I offer an alternative perspective to reading Slouching Towards Bethlehem and The Year of Magical Thinking, arguing that Didion's writing is inherently “Romantic” in its quest to make sense of the world and of the human condition. I suggest that readers of Didion should dissect her sentences, question her meanings and contribute towards her narrative with their own opinions, while using her emblems as a reference to relate, contrast and compare their own life experiences.